Mobile devices usage in retail setting: Gender and generation preferences - Cavalinhos, S.; Salgueiro, M. F.; Marques, S. (International Journal of Retail & Distribution Management, 2023)
Purpose: The tendency shows that more customers will bring and use their mobile devices in-store. This study proposes a further analysis of the complementary role of the mobile device in an in-store purchase providing a characterisation of those customers and analyses their usage preferences and behaviour intentions, presenting new insights concerning gender and generation preferences. Design/methodology/approach: Quantitative research with customers of electronic stores was conducted based on a questionnaire applied at the store’s exit. To assess the differences between genders and among generations were used the parametric T-Test and one-way ANOVA. Findings: The results demonstrate divergencies between generations when using mobile devices. In addition, they indicate that males have more intention to manage shopping tasks efficiently and consequently are less affected by in-store marketing stimuli and less predisposed to impulse purchases. Research limitations/implications: Although real customers participated, a convenience sample was used. The results should be compared with research on other retailer types. The customer shopping motivations and the types of mobile device usage should be further investigated since they can change the experience and the retailer’s outcomes. Practical implications: Contributing to related specific research areas such as shopping behaviour and technology in retail settings by showing the usage preferences, the study also provides information for retailers, especially those needing to approach the Gen Z customers, improving the development of strategies. Originality/value: This research explores further the complementary role of the mobile device in an in-store purchase. By conducting the study in a new setting, it brings new insight into a less explored, yet important sector.